Effect of Alkali-treated Bamboo Fibers on Some Mechanical Properties of Virgin High Density Polyethylene - , Pethuel O. Atanda; , Kunle J. Akinluwade; , Olanrewaju S. Adesina; , Robert A. Onwumere (Archives of Current Research International, 2017)
The study investigated effects of chemically treated bamboo fibers on some mechanical properties of virgin high density polyethylene. Bamboo fibers and particulates treated with NaOH and KOH were blended by mixing with molten high density polyethylene to produce eight (8) different composition sets for standard tensile, impact and flexural tests. Results from the tests. Results obtained indicated that 2-14% volume addition of bamboo particulates or fibers as a reinforcement to virgin HDPE, improves service properties such as Young’s modulus, UTS, toughness, flexural modulus and strength. Overall, alkali treated particulate bamboo wood demontrated improved properties over fibrous bamboo wood within the scope of conduct of the study.